Virtual learning environment in nutrition teaching: an experience report (Research, Society and Development, 2020)
With technological advances, the option of using the Virtual Learning Environment (VLE) was offered, allowing greater interactivity in the daily teaching of nutrition, encouraging educators to represent their pedagogical practices. This study aims to report the experience of using the virtual environment in nutrition education from the students' perspective. The discipline "Experimental Nutrition and Research Practices" was given to 49 students from the 6th and 7th period of the Undergraduate Course in nutrition, of which 26 answered a questionnaire with closed questions, being an open question about the use of VLE. The students considered VLE to be a tool that facilitates learning, the process of building knowledge and interaction between students, teachers and tutors, thus enriching the sharing of ideas and allowing meaningful and collaborative learning. The study revealed the need to improve the use of VLE in undergraduate nutrition education.